The Prophet’s Discussion(peace be upon him) with the Polytheists In View of the Narratives of Imam al-Sadiq (peace be upon him) (the Treaty of Hudaybiyyah as a Model) - Falah Al-Badri, Sabah (Journal of College of Education, 2022)
Discussion has been an instinct inherent to humanity throughout its long history, and it is an important method for resolving differences without resorting to violence and fighting. The unique biography of the Prophet(PBUH ) was a model for Muslims to follow, and one that was embodied in many situations. Among those situations was his dialogue with the polytheists, of which we have confined ourselves to a part of the Treaty of Hudaybiyah, which was of great importance in the course of the Islamic call. The Imams of the Ahl al-Bayt(peace be upon them) played a major role in transmitting the authentic biography of the Prophet. They were his offspring, whom God Almighty purified thoroughly. Imam al-Sadiq(PBUH) was the most frequent transmitter of the Prophet’s biography(PBUH), for well-known reasons. He cited the most important events that prompted the peace treaty, as well as those resulted from it. Therefore, our research was titled “The Prophet’s dialogue(PBUH ) with the polytheists(the Treaty of Hudaybiyyah as a model)” in the view of the narratives of Imam al-Sadiq(PBUH).